ChemInform Abstract: Broensted Acid Mediated Nitrogenation of Propargylic Alcohols: An Efficient Approach to Alkenyl Nitriles. Issue 48 (2nd December 2014) - Huang, Xiaoqiang; Jiao, Ning
Abstract A new approach to alkenyl nitriles under mild and metal‐free conditions via the direct incorporation of a nitrogen atom into propargylic alcohols is described.